Instructional and learning needs in evolution education: a multi-stakeholder needs assessment - Vanjoreeh A. Madale; Monera A. Salic-Hairulla (International Journal of Evaluation and Research in Education (IJERE), 2026)
Evolution is a foundational concept in biology, yet it remains challenging for learners and teachers alike. This study conducted a descriptive convergent mixed-methods needs assessment to examine instructional and learning needs in evolution education from the perspectives of students, teachers, and administrators. A total of 50 participants (35 students, 10 teachers, and 5 administrators) from a public senior high school completed researcher-developed questionnaires containing Likert-scale and open-ended items. Quantitative data were analyzed using descriptive statistics, while qualitative responses underwent thematic analysis, with integration occurring at interpretation. Findings indicate that students possess moderate conceptual understanding but struggle with abstract processes such as natural selection, long-term species change, and evidence interpretation, alongside gaps in science process skills. Teachers report difficulties addressing misconceptions, integrating inquiry-based practices, and accessing contextualized instructional materials. Administrators emphasize the need for laboratory resources, curriculum-aligned materials, and sustained professional development. Overall, results highlight that strengthening evolution education requires coordinated strategies that integrate structured science process skills, targeted teacher training, and institutional support systems. The study provides a multi-stakeholder framework to guide evidence-based instructional and systemic improvement in evolution education.